Algal Oil Rich in n-3 PUFA Alleviates DSS-Induced Colitis via Regulation of Gut Microbiota and Restoration of Intestinal Barrier - Xu, Zhenxia; Tang, Hu; Huang, Fenghong; Qiao, Zhixian; Wang, Xu; Yang, Chen; Deng, Qianchun (Frontiers in Microbiology, 2020)
Algal oil is rich in docosahexaenoic acid (DHA) and has various health benefits against human metabolic disorders and disease. This study aimed to investigate the effects of DHA algal oil on colonic inflammation and intestinal microbiota in dextran sulfate sodium (DSS)-induced colitis mice model. Male C57BL/6 mice was induced colitis by 2.5% DSS and followed by 2 weeks of treatment with algal oil (250 mg/kg/d or 500 mg/kg/d). The colonic inflammation was assessed by colon macroscopic damage scores, and the degree of neutrophil infiltration was evaluated by measuring tissue-associated myeloperoxidase (MPO) activity in colonic mucosa. Tight junction proteins in the colonic tissue were measured by real-time PCR and western blot. Moreover, the intestinal microbiota and shot chain fatty acids (SCFAs) were estimated by bioinformatic analysis and GC, respectively. Colonic damage due to DSS treatment was significantly ameliorated by algal oil supplementation. In addition, algal oil significantly inhibited the increases of malondialdehyde (MDA) content, MPO activity, pro-inflammatory cytokines level and tight junction proteins expression in DSS-treated mice. Furthermore, supplementation of algal oil modulated the intestinal microbiota structure in DSS induced colitis mice by increasing the proportion of the unidentified_S24_7 and decreasing the relative abundance of unidentified_Ruminococcaceae, Clostridium and Roseburia. On the analysis of SCFAs, the caecal content of acetic acid, propionic acid, isobutyric acid, buturic and the total SCFAs showed a significant increase in algal oil-administered mice. Together, these results suggested that algal oil rich in DHA inhibited the progress of DSS-induced colitis in mice by modulating the intestinal microbiota and metabolites and repairing the intestinal barrier, which may be applied in the development of therapeutics for intestinal inflammation.